Integrated primary care for patients with mental and physical multimorbidity: cluster randomised controlled trial of collaborative care for patients with depression comorbid with diabetes or cardiovascular disease. (16th February 2015) - Coventry, Peter; Lovell, Karina; Dickens, Chris; Bower, Peter; Chew-Graham, Carolyn; McElvenny, Damien; Hann, Mark; Cherrington, Andrea; Garrett, Charlotte; Gibbons, Chris J; Baguley, Clare; Roughley, Kate; et al.
Abstract : Objective To test the effectiveness of an integrated collaborative care model for people with depression and long term physical conditions. Design Cluster randomised controlled trial. Setting 36 general practices in the north west of England. Participants 387 patients with a record of diabetes or heart disease, or both, who had depressive symptoms (≥10 on patient health questionaire-9 (PHQ-9)) for at least two weeks. Mean age was 58.5 (SD 11.7). Participants reported a mean of 6.2 (SD 3.0) long term conditions other than diabetes or heart disease; 240 (62%) were men; 360 (90%) completed the trial. Interventions Collaborative care included patient preference for behavioural activation, cognitive restructuring, graded exposure, and/or lifestyle advice, management of drug treatment, and prevention of relapse. Up to eight sessions of psychological treatment were delivered by specially trained psychological wellbeing practitioners employed by Improving Access to Psychological Therapy services in the English National Health Service; integration of care was enhanced by two treatment sessions delivered jointly with the practice nurse. Usual care was standard clinical practice provided by general practitioners and practice nurses. Main outcome measures The primary outcome was reduction in symptoms of depression on the self reported symptom checklist-13 depression scale (SCL-D13) at four months after baseline assessment. Secondary outcomes included anxiety symptoms (generalised anxiety disorder 7), self management (health education impact questionnaire), disability (Sheehan disability scale), and global quality of life (WHOQOL-BREF). Results 19 general practices were randomised to collaborative care and 20 to usual care; three practices withdrew from the trial before patients were recruited. 191 patients were recruited from practices allocated to collaborative care, and 196 from practices allocated to usual care. After adjustment for baseline depression score, mean depressive scores were 0.23 SCL-D13 points lower (95% confidence interval −0.41 to −0.05) in the collaborative care arm, equal to an adjusted standardised effect size of 0.30. Patients in the intervention arm also reported being better self managers, rated their care as more patient centred, and were more satisfied with their care. There were no significant differences between groups in quality of life, disease specific quality of life, self efficacy, disability, and social support. Conclusions Collaborative care that incorporates brief low intensity psychological therapy delivered in partnership with practice nurses in primary care can reduce depression and improve self management of chronic disease in people with mental and physical multimorbidity. The size of the treatment effects were modest and were less than the prespecified effect but were achieved in a trial run in routine settings with a deprived population with high levels of mental and physical multimorbidity. Trial registration ISRCTN80309252.